In silico study of different thrombolytic agents for fibrinolysis in acute ischemic stroke - Yang,Y; Gu,B; Xu,X (Pharmaceutics, 2023)
Alteplase is the only FDA-approved drug for thrombolysis in acute ischemic stroke (AIS). Meanwhile, several thrombolytic drugs are deemed to be promising candidates to substitute alteplase. This paper evaluates the efficacy and safety of urokinase, ateplase, tenecteplase, and reteplase for intravenous AIS therapy by computational simulations of the pharmacokinetics and pharmacodynamics combined with a local fibrinolysis model. The performances of the drugs are evaluated by comparing clot lysis time, plasminogen activator inhibitor (PAI) inhibition resistance, intracranial hemorrhage (ICH) risk, and activation time from drug administration to clot lysis. Our results reveal that urokinase has the quickest lysis completion but the highest ICH risk due to excess fibrinogen depletion in systemic plasma. While tenecteplase and alteplase have very similar thrombolysis efficacy, tenecteplase has a lower risk of ICH and better resistance to PAI-1. Among the four simulated drugs, reteplase has the slowest fibrinolysis rate, but fibrinogen concentration in systemic plasma is unaffected during thrombolysis.